Plants associated with fish by Guaraníes of Misiones, Argentina - Keller, Hector Alejandro (2008)
The use of plants species for different aspects of fishing by the Guaraníes in the Selva  Paranense (forests) of Misiones, Argentina is described. The most frequent method of  fishing is through the use of various ichthyotoxic plants and these come from a  variety of forest trees, climbers and herbs. The plants used for traps and other methods of fishing are also described.